Descripción de la fertilización edáfica en el cultivo de café (Coffea arábica) en la Hacienda Chojampe en el Cantón Ventanas - Poveda Escobar, Yulitza Yimabel (2020)
The cultivation of coffee is known as the coffee tree or coffee producing plant, this is a shrub that develops in areas of the earth. In the case of Arabica coffee, it is considered the most vulnerable to pests and diseases than Robusta. Among the main coffee producing countries are Brazil and Vietnam. Coffee cultivation is of great importance at a social, economic and ecological level in Ecuador. According to FAO research, fifty percent of coffee is produced in coastal provinces. Robusta coffee is produced mainly in the Amazon, while Arabica is grown along the coast. Coffee plantations can achieve high production and better yields if they apply efficient phytosanitary control and employ the incorporation of fertilizers at the right time, in the appropriate phenological state and in the necessary doses in order to generate good development and growth of the cultivation, avoiding the susceptibility of coffee pests and diseases in the short and long term. The main objective was to analyze how edaphic fertilization in coffee cultivation (Coffea arabica) "influences phenology at the San Gabriel hacienda. The research was carried out at the Chojampe coffee farm, located in the province of Los Ríos, canton Windows. At the Chojampe coffee farm we were told that coffee has been cultivated in Ecuador since 1950 and that it is a crop that can contribute to the economic, social and environmental sector. The information obtained at the Chojampe coffee farm allows us to identify the Situations present in the crop, among them is the development of an edaphic fertilization program, incorporation of the necessary elements based on the phenology of the crop and preventive measures against the nutritional deficit that hinders the production of coffee, marketing and development of the plants During the tour they detailed the functions that each element fulfills in the cultivation of coffee as the case of Nitrogen that favors the development of coffee leaves, therefore phosphorous participates in the formation of stems, branches, flowering and the root system. While potassium helps in formation and quality of the coffee fruits.